Depredation and deteriorating condition of Shorea robusta and Terminalia alata in Bardia National Park: an imperative to address park biodiversity sustainably - Acharya, GR; Bhatta, B; Gyawali, AR (Banko Janakari, 2009)
The paradigm shift in park management from a fortress mentality to the participatory concept is represented as a major transformation in the conservation discourse in Nepal. The involvement of local people in the management of resources in national parks has been significantly effective in attaining the conservation goals of conserving wildlife without compromising the basic forest resource needs of the local people. Nevertheless, some economically important species have not been afforded due consideration during such management. This study investigates the species composition and regeneration status of Shorea robusta (Sal) and Terminalia alata (Saj) in 4 Buffer Zone community Forests of Bardia National Park in Thakurdwara VDC in 1999/2000, 2002/2003 and 2005. The results reveal that Shorea robusta (Sal) and Terminalia alata (Saj) both constituted a large proportion of species diversity but that their regeneration from seedlings to established stages were low, suggesting vulnerability of this forest and their sustainability at risk due to their dwindling conditions. Immediate management concern of these economically important forest tree species is warranted. Keywords: Biodiversity, national park, shorea robusta, sustainability, terminalia alata doi: 10.3126/banko.v19i1.2181 Banko Janakari, Vol. 19, No. 1, 37-40